Penggunaan MCK Komunal dan MCK Pribadi oleh Masyarakat Nagari Limau Lunggo Kecamatan Lembang Jaya Kabupaten Solok - Fajar Sarli; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This article was written to discover: the used and behavior of the people in using personal MCK and communal MCK in Nagari Limau Lunggo, Lembang Jaya Subdistrict, Solok Regency. This research is a descriptive with qualitative inquiry. Primary data in this research was interview with the society, and the secondary data was the archives in Limau Lunggo office. The sampling method was purposive sampling, the data was collected by interview and documentary. The data analyzed by display data, and . The result show that from 673 KK, 210 had MCK Pribadi with percentage 31,20%. A total of 463 KK used Communal MCK with a percentage of 68.80%. The number of Communal MCKs in 21 Nagari Limau Lunggo , which are scattered as many as; 12 in Jorong Banda Balai, 6 in Jorong Banda Panai, 2 in Jorong Banto, and 1 in Jorong Karatau.